DIGITAL COMMUNICATION AND LEARNING TECHNOLOGY ADOPTION DURING COVID-19 PANDEMIC - Hindina Maulida; Rizza Arge Winanta; R. Yogie Prawira W (Sean Institute, 2021)
The Covid-19 pandemic has changed the communication and learning processes by utilizing digital communication. The challenge of adopting digital communication is inevitable when supporting learning shifts from offline to online systems. However, it is necessary to consider the effectiveness factor in order to facilitate adoption. The Technology Acceptance Model (TAM) is a theoretical framework that describes how a technology can be accepted, adopted, and used by society. Two factors influence people's acceptance of technology: perceived ease of use and perceived of usefulness. In the context of learning using digital communication technology, Google Classroom is a learning technology that is considered easy because there are tutorials available that can guide users and make it easy to access. Its advantage is that it facilitates interaction and learning experiences such as the ability to upload various materials and provide direct feedback. In short, the application of the Technology Acceptance Model (TAM) theory to the adoption of digital communication technology in courageous learning during the Covid-19 pandemic can provide understanding and knowledge about aspects that contribute to the adoption and use of technology during times of crisis.